259 The Electronic Patient Record as an Enabler for Hospital Wide Delirium and Dementia Screening -Lessons Learned from a Clinical Implementation. (16th September 2019) - Chapman, Lucy; Corbett, Mel; Courtney, Grainne; Lawlor, Brian
Abstract: Background: The validated 4 As Test (4AT) cognitive screening tool was incorporated into the electronic patient record (EPR) to facilitate hospital wide delirium and dementia screening. Completion of the 4AT was mandated by its incorporation into a computer alert targeted at doctors. This alert was generated on all hospital inpatients aged 65 years and over at 24 hours into admission in keeping with the National Institute for Health and Care Excellence guidelines. An option to bypass the 4AT alert was available. Methods: Multidisciplinary clinical stakeholder workshops informed the design of the electronic cognitive screening alert. An implementation strategy was undertaken using intensive clinical engagement. On June 27 th 2018, the 4AT electronic alert was deployed. Data entries from the completed electronic 4AT assessments were extracted from the EPR facilitating descriptive statistical analysis and point prevalence analysis for delirium and dementia. Specialty-based comparisons were also made. Results: During the first 24 hours post-implementation, 4AT screening assessments were completed in 61% of instances equating to 324 completed assessments. Forty eight percent (n=155) had a score of zero suggestive of normal cognitive status. Notably, 20% assessments yielded a score reflective of possible delirium (four or more). Dementia was a recognised clinical diagnosis in 23% (n=76) of patients. One in two of these dementia patients scored four or more indicative of coexistent delirium. Conclusion: Electronic patient records can be harnessed to facilitate hospital-wide delirium and dementia screening and improve detection. This also represents a novel method to capture data for the purposes of audit and research as well as to inform and improve future directions in clinical care and resource allocation. Innovative computer-based strategies may offer future directions to augment detection of cognitive disorders in hospitalised populations.